E-PURCHASING: LANGKAH NYATA PEMERINTAH DALAM MENDUKUNG PROGRAM PENINGKATAN PENGGUNAAN PRODUK DALAM NEGERI (P3DN) - , Eny Suryani; Kandung Sapto Nugroho; Juliannes Cadith (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This article explores the transformation of government procurement of goods and services in Indonesia through e-purchasing as an effort to support the Domestic Product Use Improvement Program (P3DN). The research is conducted using a qualitative method based on literature review, where the main data sources come from various scientific documents and related regulations. The results show that e-purchasing plays an important role in improving transparency, accountability, and efficiency of the procurement process, as well as encouraging the use of local products by the government. In addition, the implementation of e-purchasing is also able to increase the competitiveness of local producers in domestic and international markets. E-purchasing is a strategic step in achieving national economic independence through optimizing the use of domestic products. Some future challenges related to the implementation of e-purchasing in supporting the P3DN program can be used as risk mitigation for the success of the Increasing the Use of Domestic Products through e-purchasing program.